The impact of Malaysian economic development on C02 emission / Shaliza Azreen Mohd Zulkifli, Noorfarah Dyana Noorazlan Ong and Rozihanim Sheikh Zain - Mohd Zulkifli, Shaliza Azreen; Noorazlan Ong, Noorfarah Dyana; Sheikh Zain, Rozihanim (Universiti Teknologi MARA, Perak, 2021)
The manufacturing industry plays an important role as one of the main contributors to Malaysian economic growth. According to the Department of Statistics Malaysia (DOSM), the value of gross output rose 5.7 percent per annum to RM1,275.8 billion in 2017 as compared to 2015 (RM1,142.0 billion). Even though greater economic activities lead to greater economic production, unfortunately, most forms of economic production generate pollution. Therefore, this study attempts to examine the relationship between economic development and CO2 emission in the context of Malaysia from year 1986 until 2016. The dependent variable used in this study is CO2 emission, while the dependent variables are economic growth, population, urbanization, and industrialization. Using the Dynamic Ordinary Least Square (DOLS) method, the results revealed the existence of the long-run relationship between economic development and CO2 emission where economic growth and urbanization show a positive significant impact towards CO2 emission.